The change of nutritional value of the fermented Eichhornia crassipes Mart meal as broiler rations - Fera Mahmilia (Indonesian Center for Animal Research and Development (ICARD), 2005)
Eichhornia crassipes Mart is one of the water plants which grows in the rivers, ricefields, water reservoirs or dams. This plant is often considered as water weeds that harm people much. This weed can be used for feeding the animal, but it has high crude fiber. Fermentation tehnology could be done to overcome the problem. E. crassipes Mart is grounded into meal and solidly fermented by mixing minerals and Trichoderma harzianum for 4 days at room temperature. The fermentation resulted the increase of nutritional value. The crude protein increases for 61.81% (from 6.31 to 10.21%) and crude fiber decreases for 18% (26.61 to 21.82%). The in vivo experiment was conducted based on completely randomized design using 80 day old broiler chicks with 5 replication. They were alotted to 4 diets containing one control without fermented E. crassipes Mart, 5, 10 and 15% of fermented E. crassipes Mart. Diets were fed ad libitum for 6 weeks. Feed intake, weight gain and feed conversion ratio, carcas and abdominal fat were observed as parameters. Result showed that no parameter were significantly affected by treatments, although the nutritional values were slightly decreasing in higher fermented E. crassipes. The fermented E. Crassipes Mart can be used up to 15% in broiler rations. Key Words: Eichhornia crassipes Mart Meal, Nutritional Value, Fermentation, Ration